Bobby Brewster's Torch - Todd, H E (Hodder and Stoughton Ltd, 1969)
A torch that flashes morse messages all by itself,and an artistic tree that paints pictures; these are just two of the extraordinary things that Bobby Brewster comes across in this collection of stories about the famous school boy.
Keywords: Juvenile fiction; Literary Criticism & Collections